Pengaruh Motivasi Terhadap Prestasi Pada Atlet Sepakbola: Literatur Review - Yuni Crissa Sumbayak; Diyya Awaliah; Dini Nur Alpiah (JURNAL ILMIAH NUSANTARA, 2024)
Achievement is the most important part of athlete development. There are several factors that can influence the performance of football athletes, including training motivation. A study shows that the percentage importance of motivation is around 69% which has an influence on achievement (Oktafiranda & Ilham, 2022). Motivation itself is one of the key factors in an athlete's success in winning a match or becoming a champion. Motivation encourages athletes to provide psychological encouragement to achieve the best achievements and performance. The aim of the research is to find out how training motivation influences the performance of football athletes. This research method uses a literature review with PICO searches in several databases such as Google Scholar, Science Direct, and Pubmed. There were 5 journals that met the criteria and showed the results that motivation, both intrinsically originating from within and extrinsically due to stimulation from outside the individual, can influence achievement, so with a p-velue <0.05, it shows quite high achievement motivation in athletes who generates an athlete's efforts to master his task, achieve maximum success, and be able to overcome obstacles. It can be concluded that motivation greatly influences the increase in performance in football athletes.